PENGGUNAAN SAJAK MATEMATIKA (CINQUAINS) PADA MATERI BANGUN DATAR - Indah Suciati (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Shape is a part of Geometry which is a branch of Mathematics consisting of triangles, squares, and polygon. Its application is often used in everyday. However, even though the concept is often encountered and used, there are still many students who experience difficulties in their understanding. To overcome this, the solution is given in the method of Cinquain